2015
DOI: 10.1073/pnas.1504964112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human mobility on the emergence of dengue epidemics in Pakistan

Abstract: The recent emergence of dengue viruses into new susceptible human populations throughout Asia and the Middle East, driven in part by human travel on both local and global scales, represents a significant global health risk, particularly in areas with changing climatic suitability for the mosquito vector. In Pakistan, dengue has been endemic for decades in the southern port city of Karachi, but large epidemics in the northeast have emerged only since 2011. Pakistan is therefore representative of many countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
401
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(424 citation statements)
references
References 33 publications
9
401
1
2
Order By: Relevance
“…ICTs and social networks can play an important role in disease, vector and outbreak reporting from the community to local and regional authorities. A handful of such technologies have been used successfully in pilot implementations and within studies, including using cell phone tower signals to track human movement for prediction of the most likely outbreak locations in Pakistan; 10 online and smart phone applications to report dengue mosquito breeding sites in Mexico 11 , Nicaragua and Colombia; and near real-time search-query data that estimate impending outbreaks globally (Google dengue-trends, DengueMap). While information gained through crowd-sourcing needs to be validated by laboratory confirmation of etiology, the power of these technologies together with the strength of communities mobilized through knowledge should be harnessed as integral aspects of national surveillance systems and for documenting the impact of vaccine introduction.…”
Section: Surveillance/outbreak Response/sero-epidemiogical Studiesmentioning
confidence: 99%
“…ICTs and social networks can play an important role in disease, vector and outbreak reporting from the community to local and regional authorities. A handful of such technologies have been used successfully in pilot implementations and within studies, including using cell phone tower signals to track human movement for prediction of the most likely outbreak locations in Pakistan; 10 online and smart phone applications to report dengue mosquito breeding sites in Mexico 11 , Nicaragua and Colombia; and near real-time search-query data that estimate impending outbreaks globally (Google dengue-trends, DengueMap). While information gained through crowd-sourcing needs to be validated by laboratory confirmation of etiology, the power of these technologies together with the strength of communities mobilized through knowledge should be harnessed as integral aspects of national surveillance systems and for documenting the impact of vaccine introduction.…”
Section: Surveillance/outbreak Response/sero-epidemiogical Studiesmentioning
confidence: 99%
“…Differential ownership of mobile phones among different sectors, particularly in low and middle income countries where much of CDR research takes place, also calls into question the representativeness of the data and thus the findings that ensue [72]. However, it has also been observed that despite biases, there a few, if any, data sources that can provide such rich spatial and temporal movement data, particularly for much-needed research in LMICs [61,64].…”
Section: Discussion Principal Findings: Opportunities and Challengesmentioning
confidence: 99%
“…Wesolowski and team [64] detailed how they complied with the laws and regulations of Pakistan and the MNO Telenor, by using only data aggregated to tehsil level (an administrative unit of Pakistan). This was processed on their behalf by Telenor employees.…”
Section: Datasets and Data Governancementioning
confidence: 99%
“…Large-scale datasets from international mobile operators are being used in the realm of big data analytics to model the spread of diseases, such as dengue [11] and cholera [12], and to map poverty [13] and mobility [14]. Data from mobile financial transactions combined with mobile surveying are also showing potential as a way to plan savings and banking interventions [15], and records derived from mobile money platforms also have significant potential value for tracking income and spending.…”
Section: Background: 'Responsible Data' and Call Detail Recordsmentioning
confidence: 99%